Cancer Immunotherapy: Advances and Challenges - Syed, Binafsha Manzoor (LIAQUAT MEDICAL RESEARCH JOURNAL, 2024)
Cancer immunotherapy has emerged as a transformative approach in cancer therapeutics, offering new hope to patients by harnessing the power of the immune system to target and eliminate cancer cells. It falls under the category of targeted therapy where an immune target i.e. molecule is identified and then immunotherapy i.e. antibodies are given to target it. Recent advances have brought a number of novel therapeutic options but they are also tagged with various challenges. These challenges include but not limited to the identification of appropriate target, later resistance to the therapy and most importantly the cost of the treatment.